BEHAVIORAL HABITUATIONOF OF SMILE, GREETINGS AND GRATITUDE OF LIBRARIANS TOWARDS SCHOOL USERS - Salsabila Mayla Nadhira Syifa; Ovi Ardilla; Abdul Lahif Sitompul; Ainun Meryna Aulia; Ika Safitri (Journal of Quality Islamic Education Research, 2024)
The school library is the heart of teaching and learning. Friendly and professional librarians will make students feel comfortable and appreciated, so they are motivated to visit the library more often. One way to show the friendliness and professionalism of librarians is to familiarize the behavior of smiling, greeting, and saying thank you to the users. This research aims to find out the behavioral habituation of smiles, greetings, greetings, and gratitude that occurs at Madrasah Aliyah Muallimin UNIVA Medan. The method used is descriptive qualitative. From the research that has been done by the researcher, the results obtained include In its application, which is done in the application at Mas Muallimin Univa Medan, it applies with tangibles aspects, namely the neat appearance of librarians. Smile applied by librarians by using a cheerful smile and a sincere smile. Greetings and salutations by librarians when visitors enter the library and give greetings, librarians readily answer the greetings with the same smile and greetings, creating a relaxed and inviting atmosphere. Acknowledgments are made when the borrowers return the borrowed books. When students or teaching staff return books to their shelves, librarians are quick to greet them with a smile and a sincere expression of gratitude